Experimental analysis on a novel low-temperature vacuum drying with induced nucleation technique for dewatering stingless bees honey - Ramli, A.S. (Taylor and Francis Inc., 2018)
Honey spoilage is a major problem in storing stingless bee honey. A new method of honey dewatering was developed using a low-temperature vacuum drying with induced nucleation technique. The researchâs objective is to investigate the performance of this method in reducing honeyâs water content. Two different dewatering temperatures were applied until honeyâs water content reached below 20. The honeyâs chemical compound beforeâafter dewatering from one of the samples was tested using nuclear magnetic resonance (NMR) analysis. The dewatering rate improves significantly with higher temperature. The NMR analysis result found no changes in chemical compound beforeâafter experiment except for ethanol. Â© 2018 Taylor & Francis